2019
DOI: 10.3892/mmr.2019.10477
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MCM2 enhances the sensitivity of ovarian cancer cell to carboplatin

Abstract: Chemotherapy is widely used for the treatment of ovarian cancer. Since chemotherapy resistance is the major cause of poor prognosis in patients with ovarian cancer, it is important to identify new methods to improve the efficacy of chemotherapy. Minichromosome maintenance complex component 2 (MCM2), which serves an essential role in DNA replication, has been recently identified as a novel proliferation marker with prognostic implications in multiple types of cancer. However, the role of MCM2 in ovarian cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…MCM2 is a component of the replicative helicase machinery that is capable of interacting with histones H3 and H4 via the N-terminal domain in the process of replication [ 15 ]. MCM2 can increase the sensitivity of ovarian cancer cells to carboplatin through p53-dependent apoptotic response, thereby improving the therapeutic application of carboplatin in ovarian cancer patients [ 16 ]. Besides, extent of HMGA1 phosphorylation has been found to be differentially expressed in response to MCM2 perturbation and has a significant role to play in modulating cell behaviors of lung cancer cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCM2 is a component of the replicative helicase machinery that is capable of interacting with histones H3 and H4 via the N-terminal domain in the process of replication [ 15 ]. MCM2 can increase the sensitivity of ovarian cancer cells to carboplatin through p53-dependent apoptotic response, thereby improving the therapeutic application of carboplatin in ovarian cancer patients [ 16 ]. Besides, extent of HMGA1 phosphorylation has been found to be differentially expressed in response to MCM2 perturbation and has a significant role to play in modulating cell behaviors of lung cancer cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggested that MCM2 might be a potential therapeutic target for HCC [ 26 ]. Furthermore, Deng et al found that MCM2 inhibition could increase the sensitivity of carboplatin in ovarian cancer cell [ 27 ]. MCM3 had similarly a high expression level in multiple cancer types, such as osteosarcoma [ 21 ], salivary gland tumors [ 28 ], and glioma [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“… 45 In other types of cancers such as ovarian and lung cancer, MCM2 was found to promote the proliferative potential of these cancer cells. 46 , 47 In our in vitro functional studies, we consistently showed that MCM2 knockdown suppressed the proliferation of HeLa and SiHa cells, suggesting that MCM2 may play an oncogenic role in the cervical cancer progression. However, the prognostic role of MCM2 in cervical cancer is still controversial among studies, as a high expression of MCM2 showed better prognosis for patients with cervical cancer as shown in our bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 68%